Altered plasma adipokine levels and in vitro adipocyte differentiation in pediatric type 1 diabetes - Verrijn Stuart, A A; Schipper, H S; Tasdelen, I; Egan, D A; Prakken, B J; Kalkhoven, E; de Jager, W (The journal of clinical endocrinology and metabolism, 2012)
Type 1 diabetes (T1D) is considered a proinflammatory condition. Adipose tissue involvement seems evident because adiponectin levels correlate with disease remission and administration of leptin suppresses the low-grade systemic inflammation in mice with T1D. Whether adipose tissue involvement in T1D already occurs at a young age is yet unknown. The aim was to explore the extent of adipokine alterations in pediatric T1D and gain more insight into the mechanisms underlying the involvement of adipose tissue. First, plasma adipokine profiling (24 adipokines) of 20 children with onset T1D, 20 children with long-standing T1D, and 17 healthy controls was performed using a recently developed and validated multiplex immunoassay. Second, the effects of diabetic plasma factors on preadipocyte proliferation and differentiation were studied in vitro. In children with onset and long-standing T1D, plasma adipokine profiling showed increased levels of various adipokines acting at the crossroads of adipose tissue function and inflammation, including CCL2/monocyte chemoattractant protein-1 and the novel adipokines cathepsin S, chemerin, and tissue inhibitor of metalloproteinase-1 (P < 0.05). Furthermore, onset and long-standing diabetic plasma significantly induced preadipocyte proliferation and adipocyte differentiation in vitro (P < 0.05). Two candidate plasma factors, glucose and the saturated fatty acid palmitic acid, did not affect proliferation or adipocyte differentiation in vitro but were found to increase CCL2 (monocyte chemoattractant protein-1) secretion by adipocytes. The adipogenic effects of diabetic plasma in vitro and the altered adipokine levels in vivo suggest adipose tissue involvement in the low-grade inflammation associated with T1D, already in pediatric patients.